Impact of radiation attenuation and temperature evolution on monomer conversion of dimethacrylatebased resins with a photobleaching photoinitiator - Mucci, Veronica Lujan (2009)
The photopolymerization process of a dimethacrylate copolymer system activated by the camphorquinone (CQ)/amine photoinitiator system (1 wt%), was experimentally studied under nonisothermal conditions in 1- and 2-mm thick samples by measuring double bond conversion, temperature rise and radiation attenuation through the sample during polymerization. The peak temperature in 1- or 2-mm thick samples irradiated at 5 mW/cm2 was 29 and 388C, respectively. The temperature evolution during polymerization was also predicted by solving the energy balance coupled with the kinetic expressions for the reaction rate. Radiation attenuation as a function of depth by the photobleachable CQ results in spatial and temporal variation in the local rates of the kinetic steps involved. General relationships for spatiotemporal variations in concentration of a photobleaching initiator, in systems where attenuation and initiator consumption are taken into account, were used to compute local polymerization rates. The effects of radiation attenuation, photobleaching of the photoinitiator and variation of cure temperature at different depths into the resin, all compete to determine the double bond consumption. The increased radiation attenuation in the 2-mm thick sample was accompanied by a higher cure temperature compared with the 1-mm thick sample, and as a result, the monomer conversion averaged over the sample thickness in the 1- and 2-mm thick samples was the same. Results obtained in this research highlight the inherent interlinking of thermal and radiation attenuation effects in bulk photopolymerizing systems. POLYM. ENG. SCI., 49:2225-2233, 2009. © 2009 Society of Plastics Engineers.